Pengembangan media video pembelajaran speaking berbasis Bahasa Ibu (Bahasa Sasak) di SMK Qamamrul Huda - Sidik, Ahmad Syukron; Fahmi, Farizan (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Based on a preliminary study at SMK Qamarul Huda Bagu class X, various problems were found, both from low grades, a less interactive learning process and the media used in English subjects, especially in the field of Speaking used by the teacher was less innovative. This research uses Research Development with the ADDIE Model which consists of 5 stages, namely: Analysis, Design, Develop, Implement, and Evaluate. The results of this study indicate that learning media based on Sasak language (mother tongue) can help students improve their speaking skills.